Essential oil constituents of needles, dry needles, inflorescences and resins of Pinus caribaea Morelet growing in Bangladesh (Bangladesh Journal of Botany, 2008)
Essential oils obtained by hydrodistillation from needles, dry needles, inflorescences and resin of Pinus caribaea Morelet were analyzed by GC-MS. Seven chemical constituents in oil of needles, 13 in dry needles, 4 in inflorescences and 6 in resin were identified. The major constituents found in the needle oil are limonene, caryophyllene and germacrene D in the dry needle oil limonene, caryophyllene oxide and caryophyllene in the inflorescences oil caryophyllene oxide, limonene and crypton and in the resin oil bicyclo[3.1.1]hept -2-ene, 2,6,6- trimethyl- (52.82%), longifolen, crypton and Î²-pinene. Key words: Pinus caribaea, Chemical composition, Essential oil, GC-MS doi:10.3329/bjb.v37i2.1735 Bangladesh J. Bot. 37(2): 211-212, 2008 (December)